Absence of maternal cell contamination in mesenchymal stromal cell cultures derived from equine umbilical cord tissue - Vackova, I; Czernekova, V; Tomanek, M; Navratil, J; Mosko, T; Novakova, Z (Placenta, 2014)
This study aimed to determine whether maternal cell contamination exists in cells derived from equine umbilical cord tissue, a perspective material for cell-based therapies in veterinary medicine. Potential maternal cell contamination was analyzed at DNA level via a set of 16 microsatellite markers in cells originating from the cord tissue of 22 foals. In these cells no maternal cell contamination was detected at a sensitivity level of 0.01%. Our results suggest that equine umbilical cord tissue-derived cells are entirely of fetal origin.
Keywords: pupečník; kultivované buňky; Mesenchymal stromal cells; Umbilical Cord; těhotenství; mikrosatelitní repetice; Mesenchymal Stem Cells; Microsatellite Repeats; Horses; Cells, Cultured; mezenchymální kmenové buňky; Maternal cell contamination; ženské pohlaví; zvířata; Umbilical cord tissue; Pregnancy; koně; Female; Microsatellite markers; Animals